Prevalence of depressive symptoms in Medicine students: the challenge of different methodologies (Research, Society and Development, 2022)
Objective: Determine the prevalence of depressive symptoms among medical students in the state of Paraná, Brazil, and compare the prevalence of these symptoms among students that use traditional and active methodologies of teaching. Methodology: A cross-sectional study was conducted, with a quantitative approach, through data collection between August and September 2020. An online form was sent, through the Google Forms platform, containing 23 questions. Students from the first to the eighth period of medical school participated, with a minimum age, from all medical schools in Paraná. Results: 250 were included. From the total, 62% uses the PBL methodology, 32% the traditional methodology and 6% uses another method. When asked if the methodology could generate depressive symptoms, 70% of the participants believe that there is a relation between the methodology and depressive symptoms. Conclusion: Although depressive symptoms can be triggered by the teaching methodology and are prevalent among medical students, the results shows that there is no statistical difference between the methodologies.